Solution of Recurrence relation to find a series expression

조회 수: 9 (최근 30일)
MINATI
MINATI 2020년 1월 7일
편집: MINATI 2020년 1월 7일
syms x k r f(x) g(x) a b beta b1 M L
syms F(k) G(k)
F(0)=0;F(1)=1;F(2)=a/2;G(0)=0;G(1)=1/2;G(2)=b/2;b1=1/beta;
%%%%dnf=diff(f,x,n)
d1f=(k+1)*F(k+1);d2f=(k+1)*(k+2)*F(k+2);d3f=(k+1)*(k+2)*(k+3)*F(k+3);
d1g=(k+1)*G(k+1);d2g=(k+1)*(k+2)*G(k+2);d3g=(k+1)*(k+2)*(k+3)*G(k+3);
fd2f=symsum(((k-r+1)*(k-r+2)*F(r)*F(k-r+2)),r,0,k);%%% f*d2f
gd2g=symsum((k-r+1)*(k-r+2)*G(r)*G(k-r+2),r,0,k);fd2g=symsum((k-r+1)*(k-r+2)*F(r)*G(k-r+2),r,0,k);
gd2f=symsum((k-r+1)*(k-r+2)*G(r)*F(k-r+2),r,0,k); d1fd1f=symsum((k-r+1)*(r+1)*F(r+1)*F(k-r+1),r,0,k); %%(d1f)^2
d1gd1g=symsum((k-r+1)*(r+1)*G(r+1)*G(k-r+1),r,0,k);
%%%%%%%
eqn1=simplify((1+b1)*d3f-d1fd1f+fd2f+gd2f-(M+L)*d1f==0);
eqn2=simplify((1+b1)*d3g-d1gd1g+fd2g+gd2g-(M+L)*d1g);eqns=[eqn1 eqn2];
solve([eqns,{F(k+3),G(k+2)}])
f=sum(x^k*F(k),k,0,inf);g=sum(x^k*G(k),k,0,inf);
%%%%%%%%%
Using the above code (ofcourse after modification), I want to solve the recurrence relations {F(k+3),G(k+2)} which contains series expression
and using given condition (F(0)=0;F(1)=1;F(2)=a/2;G(0)=0;G(1)=1/2;G(2)=b/2;) to find f and g (SERIES FORM)
OR
the attched pdf (similar problem) can be followed
Thanks

답변 (0개)

카테고리

Help CenterFile Exchange에서 Calculus에 대해 자세히 알아보기

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by